ANALISIS PUBLIC DISPLAY OF AFFECTION (PDA) MELALUI INTERAKSI HUBUNGAN TEMAN SEBAYA PADA MEDIA SOSIAL INSTAGRAM - Yolanda Ulandari Linzonia, - (2021)
One of the media that facilitates someone to do Public Display of Affection (PDA) boldly is Instagram. Intimacy with physical contact, intimate texts and private moments, especially with regard to couples who are in a romantic relationship, is recorded and displayed visually on Instagram. There are and rampant PDA actions with the presence in Indonesian society which has a culture of upholding social values and norms, then this PDA can later be a bad thing, especially if it is done on social media which of course we cannot filter out anyone who sees and imitates what is uploaded on social media. Instagram. Based on this background, this study seeks to find out how PDA acts on Instagram in adolescents in Bekasi City, the perception of adolescents who have romantic relationships in Bekasi City regarding PDA actions on Instagram, and the impact of relationships with peers on the tendency to do PDA on Instagram in adolescents, Bekasi city. The research method used is qualitative phenomenology. This study resulted: the form of PDA action on adolescents in Bekasi City is in the form of videos, photos and boomerangs on insta-story and feeds with physical touch and intimate text caused by encouragement from peers, teenagers who take PDA actions perceive that doing PDA is a which is reasonable as long as it does not go beyond reasonable limits and this PDA act is recognized that it can affect the dating behavior of other children and adolescents, PDA's actions have an impact on the surrounding environment, themselves and relationships with peers. Keywords: Instagram, Peer Interaction, Public Display Of Affection (PDA)